Carbon Vacancies in a Melon Polymeric Matrix Promote Photocatalytic Carbon Dioxide Conversion. Issue 4 (20th December 2018) - Yang, Pengju; Zhuzhang, Hangyu; Wang, Ruirui; Lin, Wei; Wang, Xinchen
Abstract: Photosynthetic conversion of CO2 into fuel and chemicals is a promising but challenging technology. The bottleneck of this reaction lies in the activation of CO2, owing to the chemical inertness of linear CO2 . Herein, we present a defect‐engineering methodology to construct CO2 activation sites by implanting carbon vacancies (CVs) in the melon polymer (MP) matrix. Positron annihilation spectroscopy confirmed the location and density of the CVs in the MP skeleton. In situ diffuse reflectance infrared Fourier transform spectroscopy and a DFT study revealed that the CVs can function as active sites for CO2 activation while stabilizing COOH* intermediates, thereby boosting the reaction kinetics. As a result, the modified MP‐TAP‐CVs displayed a 45‐fold improvement in CO2 ‐to‐CO activity over the pristine MP. The apparent quantum efficiency of the MP‐TAP‐CVs was 4.8 % at 420 nm. This study sheds new light on the design of high‐efficiency polymer semiconductors for CO2 conversion. Abstract : Defects that overcome deficiency : A steam engineering strategy was developed to construct carbon vacancies (CVs) in a melon‐based carbon nitride polymer matrix. The CVs in the material effectively promoted the activation of CO2 while prolonging the charge lifetime of the carbon nitride polymer, thus promoting CO2 reduction (see picture).